2020
DOI: 10.3390/molecules25204848
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Phorbazole B

Abstract: Phorbazoles are polychlorinated heterocyclic secondary metabolites isolated from a marine sponge and several of these natural products have shown inhibitory activity against cancer cells. In this work, a synthesis of the trichlorinated phorbazole B using late stage electrophilic chlorination was developed. The synthesis relied on the use of an oxazole precursor, which was protected with an iodine in the reactive 4-position, followed by complete chlorination of all pyrrole positions. Attempts to prepare phorbaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…490 A similar state of affairs exists following the total synthesis of the reported structure of nagelamide D. 491 The rst total syntheses of several other alkaloids have also been achieved. [492][493][494][495][496] Preparation of two semi-synthetic alkaloid libraries were reported in 2020; the rst utilised 290 mg of psammaplysin F from only 46 g of freeze-dried Hyattella to probe prostate cancer cells using multiparametric quantitative single-cell imaging, 497 while the other exploited 780 mg of renieramycin M from 18 kg of Xestospongia to synthesise two series of compounds, many of which exhibit potent (low nM) activity against H292 cells. 498 The total syntheses of several pyridinium alkaloids, along with in-depth spectroscopic analysis using various solvent blends, has revealed that xestocyclamine A is in fact the enantiomer of ingenamine, a conclusion supported by X-ray diffraction data.…”
Section: Reviewmentioning
confidence: 99%
“…490 A similar state of affairs exists following the total synthesis of the reported structure of nagelamide D. 491 The rst total syntheses of several other alkaloids have also been achieved. [492][493][494][495][496] Preparation of two semi-synthetic alkaloid libraries were reported in 2020; the rst utilised 290 mg of psammaplysin F from only 46 g of freeze-dried Hyattella to probe prostate cancer cells using multiparametric quantitative single-cell imaging, 497 while the other exploited 780 mg of renieramycin M from 18 kg of Xestospongia to synthesise two series of compounds, many of which exhibit potent (low nM) activity against H292 cells. 498 The total syntheses of several pyridinium alkaloids, along with in-depth spectroscopic analysis using various solvent blends, has revealed that xestocyclamine A is in fact the enantiomer of ingenamine, a conclusion supported by X-ray diffraction data.…”
Section: Reviewmentioning
confidence: 99%
“…Phorbazoles, isolated in small amounts from a sample collected in South Africa, differ themselves only by the presence and/or position of the chlorine atoms, and their structures were elucidated using mono-and bi-dimensional NMR data coupled with X-ray diffraction studies [34]. In 2020, the total synthesis of the trichlorinated phorbazole B (10) has been realized in six steps (overall yield of 23%) using an oxazole as precursor and late stage electrophilic chlorination as key mechanism [35],while a synthesis of phorbazole C was reported in 2001 and relied on pyrrole as a precursor [36].…”
Section: Phorbazolesmentioning
confidence: 99%
“…clathrata (Levi) [22]. Recently, the chemical preparation of phorbazole B (13) has been achieved by simple catalytic chlorination and iodization to protect the oxazole ring [23]. The first chemical analysis of the marine mollusc Aldisa andersoni, collected off Muttom coast, (Kanyakumari, India) afforded two new cytotoxic phorbazole analogs, 9-chloro-phorbazole D ( 16) and N1-methyl-phorbazole A (17), as well as phorbazoles A (2), B (13) and D (15) [24].…”
Section: Peptides 21 Linear Peptidesmentioning
confidence: 99%
“…Two novel linear and achiral polyketide-peptides, ariakemicins A (18) and B (19), were obtained as an inseparable mixture from one marine gliding bacterium Rapidithrix sp., collected off the muddy land alongside the Ariake Inland Sea, and displayed selectively antimicrobial activities against Gram-positive bacteria (Brevibacterium sp., S. aureus, and Bacillus subtilis), and weak cytotoxicity against cancer cell lines A549 and BHK [25]. Breitfussins A-H (20)(21)(22)(23)(24)(25)(26)(27) were the first marine natural products containing an indole-oxazolepyrrole framework from hydrozoan Thuiaria breitfussi inhabits in the Arctic ocean, and were found to excellently inhibit PIM1 and DRAK1 kinases [26,27]. Furthermore, breitfussin C (22) strongly exhibited a cytotoxic effect on cancer cell lines (MCF-7, HT-29, MOLT-4, MV-4-11 and MRC-5).…”
Section: Peptides 21 Linear Peptidesmentioning
confidence: 99%